A facile synthesis of an Fe/N-doped ultrathin carbon sheet for highly efficient oxygen reduction reaction. Issue 23 (26th October 2020) - Zhao, Pingping; Mou, Qiuxiang; Liu, Xinghai; Li, Houbin; Cheng, Gongzhen
Abstract : Fe/N-Doped ultrathin carbon sheet was synthesized. Fe3 C/NC-800 exhibited an outstanding behavior toward ORR catalysis with a catalyst loading of 150 μg cm −2, which surpassed most of the non-precious metal electrocatalysts reported. Abstract : The search for alternatives to Pt catalysts with a high density of active sites to achieve an enhancement in the oxygen reduction reaction (ORR) is essential for the utilization of fuel cell and metal–air batteries. Herein, we report the facile synthesis of an ultrathin carbon sheet by calcining Fe-based precursors and melamine. Diverse kinds of Fe species with sizes ranging from atomic stacks to the nano-order have been established in Fe3 C/NC-800. Thanks to the high density of the active sites, good conductance, as well as the perfect pore structure, outstanding performance can be achieved at a very low mass loading of 150 μg cm −2 in both alkaline and acid solutions. Consequently, Fe3 C/NC-800 showed a half-wave potential that was ca. 20 mV more positive than that of commercial Pt/C in 0.1 M KOH, and surpassed most of the non-precious metal electrocatalysts reported in 0.1 M HClO4 .